Enlightenment and political fiction - Miller, Cecilia (Routledge, 2016)
Don Quixote (1605, 1615), rationality, and forms of government – Simplicissimus (1668, 1669), religious toleration, and friendship – Gulliver's travels (1726, amended 1735), science, and social class – Candide (1759), sexuality, and the modern individual – The betrothed (1825-1827, 1840-1842), revolution, and the perfectibility of the human mind – Conclusion
Literaturangaben. - Index
Keywords: Fiction; Politics and literature; Literature and society; Reason in literature; Emotions in literature; Enlightenment